MASTERING PRONUNCIATION: THE INFLUENCE OF THE TFLAT APPLICATION ON STUDENTS' PRONUNCIATION ABILITY - Tiara Vidia; Pipit Novita (LPPM Universitas PGRI Jombang, 2024)
This article aims to demonstrate how to influence students speaking skills through TFLAT application. This study used a quantitative method with pre-Experimental research design. The pre-test and post-test were both instruments as collecting data. The population was one class of eleven grade from SMK Muhammadiyah 02 Tangerang Selatan. The t-test was used for statistical analysis of the data. The analysis findings indicate that students averaged a score of 78.40. According to the statistical calculations show, the results to (t-value) > t (t-table) obtained are 19,365 while the t-table is 2,080 with a significant level of 5% (0.05) because the t-value is higher than the t-table than the alternative hypothesis (H1) was accepted while the (H0) was rejected. Based on the results of this analysis study concludes that TFLAT application is an effective application to influence students’ pronunciation ability.